A NOVEL MODEL FOR THE CALCULATION OF SAFETY STOCK OF PERISHABLE PRODUCTS WITH A TOTAL WASTE CONSTRAINT - Yigit, Fatih; Esnaf, Sakir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Perishable products cover a high percentage of all goods. The variability, long lead times, risk period, and high service level increase the safety stock level. An increase in safety stock will also increase the probability of perished products because of the increased probability of sales of less than stock during shelf life. This study proposes a model for calculating safety stocks of perishable products besides showing the effect of perishability on service level. The effects of long lead times, risk periods, high sales and lead-time variance, and short shelf life adversely affect perished products. The study investigates and proposes a novel model for calculating total expected waste and costs with a waste quantity constraint. A real-life example compares a proposed model with waste constraints and the traditional safety stock model based on costs and waste quantity. The case study shows the better results of the proposed models.